Polyphosphate positive electrode material and preparation method thereof, and secondary battery

By using a multi-layer cladding structure and carbon cladding layer in the lithium manganese iron phosphate positive electrode material, the problem of poor conductivity is solved and the comprehensive electricity with high conductivity, energy density and compaction density is achieved Improved chemical performance.

CN115036466BActive Publication Date: 2025-02-11SHENZHEN DYNANONIC CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210621727.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-06-02
Publication Date
2025-02-11
Estimated Expiration
2042-06-02

AI Technical Summary

Technical Problem

The electrochemical properties of the existing lithium manganese iron phosphate cathode materials need to be further improved, and the conductivity is poor, making it difficult to fully exert the performance of the material.

Method used

It adopts a polyphosphate positive electrode material, which includes several single-core, multi-shell lithium manganese iron phosphate composite materials, and the composite material consists of lithium iron phosphate or lithium manganese iron phosphate core, multi-layer lithium manganese iron phosphate coating and carbon coating. The particle size and content of manganese element in the lithium manganese ferrophosphate coating decrease radially to ensure conductivity and compaction density.

Benefits of technology

It improves the conductivity, energy density and compaction density of the polyphosphate cathode material, and has excellent comprehensive electrochemical performance, extending the service life and energy retention rate of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115036466B_ABST
    Figure CN115036466B_ABST
Patent Text Reader

Abstract

The present application belongs to the technical field of battery materials, and in particular, relates to a polyphosphate positive electrode material and a preparation method thereof, as well as a secondary battery. Among them, the polyphosphate positive electrode material includes several single-core multi-shell lithium iron manganese phosphate composite materials, including a lithium iron phosphate or lithium iron manganese phosphate core, multiple lithium iron manganese phosphate coating layers, and an outermost carbon coating layer; the particle size of the lithium iron manganese phosphate particles in the multiple lithium iron manganese phosphate coating layers decreases radially from the inside to the outside, and the content of manganese element increases radially from the inside to the outside; the number of layers of the lithium iron manganese phosphate coating layers in several single-core multi-shell lithium iron manganese phosphate composite materials is the same or different; the core particle size is different, and the thickness of each coating layer is different. The polyphosphate positive electrode material of the present application is achieved through the synergistic effect of several single-core multi-shell lithium iron manganese phosphate composite materials with the same or similar structure and different sizes, so that the positive electrode material has comprehensive electrochemical properties such as high conductivity, high energy density, and high compaction density.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of battery materials, and in particular relates to a polyphosphate positive electrode material and a preparation method thereof, and a secondary battery. Background Art

[0002] Lithium-ion battery is an energy storage device that is widely used in the field of energy storage, power batteries and portable electronic devices. Lithium-ion batteries have advantages such as high operating voltage, low self-discharge and good safety. Lithium-ion batteries are mainly composed of positive electrode materials, negative electrode materials, electrolytes, diaphragms and casings. The positive electrode materials mainly include lithium cobalt oxide, lithium manganese oxide, nickel-manganese binary system, nickel-cobalt-manganese ternary system, nickel-cobalt-aluminum ternary system, lithium iron phosphate, lithium manganese iron phosphate, etc. Among them, lithium iron phosphate LiFePO4 has the advantages of low cost, high safety and good cycle life. Lithium manganese iron phosphate (LMFP, LiMn 1~ x Fe x Lithium iron phosphate (LFP4) is developed on the basis of lithium iron phosphate modification. It is a solid solution material composed of lithium iron phosphate and lithium manganese phosphate. It has similar properties to lithium iron phosphate and lithium manganese phosphate, and has good thermal stability and chemical stability. Compared with lithium iron phosphate, lithium manganese iron phosphate has a higher voltage platform, and its electrical conductivity and lithium ion conductivity are improved compared with lithium manganese phosphate. It is a positive electrode material that deserves great attention. However, the conductivity of a single lithium manganese iron phosphate material is very poor. Pure lithium manganese iron phosphate is almost an insulator, and it is difficult to give full play to the electrochemical properties of the material.

[0003] Although the conductivity of the material has been improved to a certain extent after carbon coating, the conductivity of the material is still very poor, and the electrochemical performance of the material is still difficult to fully exert. The existing multi-layer coating structure of lithium manganese iron phosphate positive electrode material, although it finally achieves the effect of improving compaction, does not fully release the electrochemical performance of the material, which limits its application. Summary of the invention

[0004] The purpose of the present application is to provide a polyphosphate positive electrode material and a preparation method thereof, as well as a secondary battery, which aims to solve the problem that the electrochemical performance of the existing lithium manganese iron phosphate positive electrode material needs to be further improved to a certain extent.

[0005] In order to achieve the above application purpose, the technical solution adopted in this application is as follows:

[0006] In a first aspect, the present application provides a polyphosphate positive electrode material, which includes a plurality of single-core multi-shell lithium iron manganese phosphate composite materials; the single-core multi-shell lithium iron manganese phosphate composite material includes a lithium iron phosphate or lithium iron manganese phosphate core, a plurality of lithium iron manganese phosphate coating layers coated on the outer surface of the core, and a carbon coating layer coated on the outermost layer of the single-core multi-shell lithium iron manganese phosphate composite material; the lithium iron manganese phosphate coating layer includes lithium iron manganese phosphate particles; in the plurality of lithium iron manganese phosphate coating layers, the particle size of the lithium iron manganese phosphate particles decreases radially from the inside to the outside; the content of manganese element in the lithium iron manganese phosphate particles in the plurality of lithium iron manganese phosphate coating layers increases radially from the inside to the outside; the number of layers of the lithium iron manganese phosphate coating layers in the plurality of the single-core multi-shell lithium iron manganese phosphate composite materials is the same or different; the core particle size of the plurality of the single-core multi-shell lithium iron manganese phosphate composite materials is different, and the thickness of each coating layer is different.

[0007] In a second aspect, the present application provides a method for preparing a polyphosphate positive electrode material, comprising the following steps:

[0008] preparing lithium iron phosphate particles and lithium manganese iron phosphate particles with different manganese to iron ratios respectively; wherein the higher the manganese content in the lithium manganese iron phosphate particles, the smaller the particle size;

[0009] The lithium iron phosphate or lithium iron manganese phosphate particles are used as the inner core, and the lithium iron manganese phosphate particles with different manganese to iron ratios are coated on the outer surface of the inner core in sequence according to the rule that the manganese content increases radially from the inside to the outside, to form a plurality of lithium iron manganese phosphate coating layers;

[0010] Preparing a carbon coating layer on the surface of the outermost lithium manganese iron phosphate coating layer to obtain a first composite material;

[0011] A plurality of single-core multi-shell lithium manganese iron phosphate composite materials of different sizes are prepared by the same method, wherein the number of layers of the lithium manganese iron phosphate coating layer in the plurality of single-core multi-shell lithium manganese iron phosphate composite materials is the same or different; the core particle size of the plurality of single-core multi-shell lithium manganese iron phosphate composite materials is different, and the thickness of each coating layer is different;

[0012] A plurality of the single-core multi-shell lithium manganese iron phosphate composite materials are mixed to obtain a polyphosphate positive electrode material.

[0013] In a third aspect, the present application provides a secondary battery, wherein the positive electrode material of the secondary battery comprises the above-mentioned polyphosphate positive electrode material, or comprises the polyphosphate positive electrode material prepared by the above-mentioned method.

[0014] The polyphosphate positive electrode material provided in the first aspect of the present application includes a plurality of mononuclear multi-shell lithium iron manganese phosphate composite materials, which use large-particle lithium iron phosphate or high-iron and low-manganese lithium iron phosphate as the core carrier, and have the characteristics of good high rate performance, excellent low temperature performance, high compaction density, good cycle performance, long service life, high energy retention rate, good structural stability, high safety performance, etc. Then, the lithium iron manganese phosphate particles are coated on the outer surface of the core in the order of manganese content from low to high and particle size from large to small to form a plurality of lithium iron manganese phosphate coating layers. The high manganese content material with poor discharge performance is coated on the outside in the form of small particle size, shortening the distance between the material and the electrolyte, thereby shortening the ion migration transmission channel and ensuring the conductive performance of the composite material. And the particle size of the particles in the lithium iron manganese phosphate coating layer decreases from the inside to the outside, and the particles with small particle size on the outside can be filled in the larger particle gap of the previous coating layer to improve the compaction density of the composite material. In addition, the number of layers of the lithium iron manganese phosphate coating layer in some of the single-core multi-shell lithium iron manganese phosphate composite materials in the polyphosphate positive electrode material of the present application is the same or different; the kernel particle size of some of the single-core multi-shell lithium iron manganese phosphate composite materials is different, and the thickness of each coating layer is different. That is, some of the single-core multi-shell lithium iron manganese phosphate composite materials have similar or identical structures, but the sizes of the kernel and the coating shell are different. The gradation is formed by some of the single-core multi-shell lithium iron manganese phosphate composite materials, which not only ensures the electrochemical performance of the polyphosphate positive electrode material, but also helps to improve the overall compaction density of the polyphosphate positive electrode material and improve the energy density of the polyphosphate positive electrode material. The polyphosphate positive electrode material has high electrical conductivity, high energy density, high compaction density, and excellent comprehensive electrochemical performance.

[0015] The second aspect of the present application provides a method for preparing a polyphosphate positive electrode material. After preparing lithium iron phosphate particles and lithium iron manganese phosphate particles with different manganese-iron ratios, lithium iron phosphate or lithium iron manganese phosphate particles are used as the core, and the lithium iron manganese phosphate particles are sequentially coated on the outer surface of the core in a manner that the manganese content increases radially from the inside to the outside to form multiple lithium iron manganese phosphate coating layers. Then a carbon coating layer is prepared on the outermost side to obtain a single-core multi-shell lithium iron manganese phosphate composite material, that is, the first composite material. Then, a number of single-core multi-shell lithium iron manganese phosphate composite materials of different sizes are prepared in the same way, and the number of layers of the lithium iron manganese phosphate coating layer in the single-core multi-shell lithium iron manganese phosphate composite materials is the same or different; the core particle size of the single-core multi-shell lithium iron manganese phosphate composite materials is different, and the thickness of each coating layer is different. Then, a number of composite materials with the same or similar structure but different sizes are mixed to obtain a polyphosphate positive electrode material. The preparation process is simple and suitable for large-scale industrial production and application. The prepared polyphosphate positive electrode material has high conductivity, high energy density, high compaction density and excellent comprehensive electrochemical performance through the synergistic effect of three different sizes of single-core multi-shell lithium manganese iron phosphate composite materials with the same or similar structures.

[0016] The secondary battery provided in the third aspect of the present application comprises the above-mentioned polyphosphate positive electrode material, which, through the synergistic effect of a number of single-core multi-shell lithium manganese iron phosphate composite materials of the same or similar structure but different sizes, makes the polyphosphate positive electrode material have high conductivity, high energy density, high compaction density, and excellent comprehensive electrochemical performance. Thus, the electrochemical performance of the secondary battery is improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0018] Figure 1 It is a schematic flow chart of the method for preparing the polyphosphate positive electrode material provided in the embodiment of the present application. DETAILED DESCRIPTION

[0019] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0020] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.

[0021] In the present application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b or c", or "at least one of a, b and c", can all represent: a, b, c, a~b (i.e. a and b), a~c, b~c, or a~b~c, where a, b, c can be single or multiple, respectively.

[0022] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.

[0023] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "an" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0024] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass in the embodiment description of the present application can be μg, mg, g, kg and other mass units known in the chemical industry.

[0025] The terms "first" and "second" are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. For example, without departing from the scope of the embodiments of the present application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features.

[0026] The first aspect of the embodiment of the present application provides a multi-phosphate positive electrode material, which includes a plurality of single-core multi-shell lithium iron manganese phosphate composite materials; the single-core multi-shell lithium iron manganese phosphate composite material includes a lithium iron phosphate or lithium iron manganese phosphate core, a plurality of lithium iron manganese phosphate coating layers coated on the outer surface of the core, and a carbon coating layer coated on the outermost layer of the single-core multi-shell lithium iron manganese phosphate composite material; the lithium iron manganese phosphate coating layer includes lithium iron manganese phosphate particles; in the plurality of lithium iron manganese phosphate coating layers, the particle size of the lithium iron manganese phosphate particles decreases radially from the inside to the outside; the manganese content of the lithium iron manganese phosphate particles in the plurality of lithium iron manganese phosphate coating layers increases radially from the inside to the outside; the number of lithium iron manganese phosphate coating layers in the plurality of single-core multi-shell lithium iron manganese phosphate composite materials is the same or different; the core particle size of the plurality of single-core multi-shell lithium iron manganese phosphate composite materials is different, and the thickness of each coating layer is different.

[0027] The polyphosphate positive electrode material provided in the first aspect of the embodiment of the present application includes a plurality of single-core multi-shell lithium iron manganese phosphate composite materials, which include a lithium iron phosphate or lithium iron manganese phosphate core, a plurality of lithium iron manganese phosphate coating layers with increasing manganese content, and an outermost carbon coating layer from the inside to the outside; and the particle size of the lithium iron manganese phosphate particles in the plurality of lithium iron manganese phosphate coating layers decreases radially from the inside to the outside. Since the higher the manganese content in the lithium iron manganese phosphate particles, the higher the material voltage platform, the worse the discharge performance, the particle size needs to be reduced, but the reduction in particle size will lead to a decrease in compaction density. Therefore, in the embodiment of the present application, first, large-particle lithium iron phosphate or lithium iron manganese phosphate with high iron and low manganese content is used as the core carrier, which has the characteristics of good high rate performance, excellent low temperature performance, high compaction density, good cycle performance, long service life, high energy retention rate, good structural stability, and high safety performance. Then, the lithium iron manganese phosphate particles are coated on the outer surface of the core in the order of manganese content from low to high and particle size from large to small to form multiple lithium iron manganese phosphate coating layers. The high manganese content material with poor discharge performance is coated on the outside in the form of small particle size, shortening the distance between the material and the electrolyte, thereby shortening the ion migration transmission channel and ensuring the conductivity of the composite material. In addition, the particle size of the particles in the lithium iron manganese phosphate coating layer decreases from the inside to the outside, and the particles with small particle size on the outside can be filled in the larger particle gap of the previous coating layer, thereby improving the compaction density of the composite material. In addition, the carbon coating layer in the single-core multi-shell lithium iron manganese phosphate composite material, as well as the lithium iron phosphate or lithium iron manganese phosphate core and the carbon coating structure in the lithium iron manganese phosphate can not only improve the stability of the particles, but also help to improve the conductivity of the material. In addition, the number of layers of lithium iron manganese phosphate coating layers in several single-core multi-shell lithium iron manganese phosphate composite materials in the polyphosphate positive electrode material of the present application embodiment is the same or different; the core particle size of several single-core multi-shell lithium iron manganese phosphate composite materials is different, and the thickness of each coating layer is different. That is, a plurality of single-core multi-shell lithium manganese iron phosphate composite materials have similar or identical structures, but the sizes of the core and the coating shell are different. The plurality of single-core multi-shell lithium manganese iron phosphate composite materials form a gradation, which not only ensures the electrochemical performance of the polyphosphate positive electrode material, but also helps to improve the overall compaction density of the polyphosphate positive electrode material and improve the energy density of the polyphosphate positive electrode material. The polyphosphate positive electrode material has high conductivity, high energy density, high compaction density, and excellent comprehensive electrochemical performance.

[0028] In some embodiments, the polyphosphate positive electrode material includes three single-core multi-shell lithium manganese iron phosphate composite materials with the same structure but different sizes, which are respectively a first composite material, a second composite material and a third composite material. A good gradation relationship can be formed by three single-core multi-shell lithium manganese iron phosphate composite materials with the same or similar structures but different sizes, which is conducive to improving the overall compaction density of the polyphosphate positive electrode material and improving the energy density of the polyphosphate positive electrode material.

[0029] In some embodiments, in the first composite material, the second composite material and the third composite material, the ratio of the core particle size is (1-1.05):(2-2.1):(4-4.2), and the ratio of the thickness of each coating layer is (1-1.05):(2-2.1):(4-4.2); that is, the first composite material, the second composite material and the third composite material have the same number of layers and materials of the core and coating layer, but the core particle size and the thickness of each coating layer have a proportional relationship of (1-1.05):(2-2.1):(4-4.2). This proportional relationship makes the first composite material, the second composite material and the third composite material present three different sizes. By using three composite materials with the same or similar structures but different sizes as polyphosphate positive electrode materials, the small-sized composite material can be filled in the gaps of the large-sized composite materials to form a gradation, which not only ensures the electrochemical properties of the polyphosphate positive electrode material, but also helps to improve the overall compaction density of the polyphosphate positive electrode material and improve the energy density of the polyphosphate positive electrode material.

[0030] In some embodiments, in the polyphosphate positive electrode material, the mass ratio of the first composite material, the second composite material and the third composite material is 1: (2-4): (5-7). The first composite material, the second composite material and the third composite material in the embodiment of the present application have a ratio of (1-1.05): (2-2.1): (4-4.2) of the core particle size and the thickness of each coating layer, and have the same or similar phase structure but different sizes. They are graded according to the mass ratio of 1: (2-4): (5-7), so that there is a better gradation relationship between the three sizes of composite materials, which is more conducive to improving the compaction density and electrochemical performance of the polyphosphate positive electrode material. In some specific embodiments, in the polyphosphate positive electrode material, the mass ratio of the first composite material, the second composite material and the third composite material includes but is not limited to 1: 2: 5, 1: 2: 6, 1: 2: 7, 1: 3: 5, 1: 3: 6, 1: 3: 7, 1: 4: 5, 1: 4: 6, 1: 4: 7, etc.

[0031] In some embodiments, the particle size ratio of the first composite material, the second composite material and the third composite material is (1.8-8): (3-16): (7-32), and the three composite materials with this particle size ratio can form a continuous gradation, and the composite particles are distributed continuously from large to small, and each level has an appropriate proportion. The positive active mixed material formed according to this particle size ratio is more conducive to improving the compaction density and overall electrochemical performance of the polyphosphate positive electrode material. In some embodiments, the particle size ratio of the first composite material, the second composite material and the third composite material includes but is not limited to (2-7): (3-15): (8-31), (2-6): (3-15): (8-31), (2-5): (3-14): (8-30), (3-7): (4-15): (10-31), etc.

[0032] In some embodiments, the particle size of the first composite material is 1.8 to 8 μm; the particle size of the second composite material is 3 to 16 μm; and the particle size of the third composite material is 7 to 32 μm. The particle sizes of the first composite material, the second composite material, and the third composite material in the embodiment of the present application not only ensure the electrochemical properties such as the conductivity and energy density of the polyphosphate positive electrode material, but also help to improve the compaction density of the polyphosphate positive electrode material. In some specific embodiments, the particle size of the first composite material includes but is not limited to 1.8 μm, 3.5 μm, 4 μm, 8 μm, 6 μm, etc.; the particle size of the second composite material includes but is not limited to 3.5 μm, 7 μm, 10 μm, 13 μm, 16 μm, etc.; the particle size of the third composite material is 7 μm, 14 μm, 10 μm, 17 μm, 20 μm, 25 μm, 30 μm, 32 μm, etc.

[0033] In some embodiments, the molar ratio of manganese to iron in the polyphosphate positive electrode material is 6:4, that is, in the polyphosphate positive electrode material formed by the first composite material, the second composite material and the third composite material, the molar ratio of manganese to iron is 6:4, which is conducive to ensuring the comprehensive performance of the polyphosphate positive electrode material, such as conductivity, energy density, and compaction density. If the manganese content increases, the discharge efficiency and compaction density of the polyphosphate positive electrode material will be reduced; if the manganese content decreases, the electrochemical properties such as energy density of the polyphosphate positive electrode material will be reduced.

[0034] In some embodiments, lithium iron phosphate or lithium iron manganese phosphate is used as the core, and the molar ratio of manganese to iron in the core is (0-1): (2-9); due to the long lithium ion transmission channel of the core particles, the embodiment of the present application uses lithium iron phosphate or lithium iron manganese phosphate with high iron and low manganese as the core, which is beneficial to improve the conductivity by increasing the iron content, thereby improving the electrical properties of the composite material. In some specific embodiments, lithium iron manganese phosphate is used as the core, and the molar ratio of manganese to iron in the core is 1: (2-9), specifically, the molar ratio of manganese to iron includes but is not limited to 1: 2, 1: 3, 1: 4, 1: 5, 1: 6, 1: 7, 1: 8 or 1: 9, etc.

[0035] In some embodiments, the molar ratio of manganese to iron in the multiple lithium iron manganese phosphate coating layers is (1-9): (9-1). In the multiple lithium iron manganese phosphate coating layers of the present application, the molar ratio of manganese to iron in the lithium iron manganese phosphate particles is (1-9): (9-1), and the multiple coating layers are arranged in a radially increasing pattern from inside to outside according to the manganese content.

[0036] In some embodiments, the polyphosphate positive electrode material includes at least one single-core multi-shell lithium manganese iron phosphate composite material comprising eight lithium manganese iron phosphate coating layers, wherein the molar ratio of manganese element to iron element in the eight lithium manganese iron phosphate coating layers is 1: (9-8), 2: (8-7), 3: (7-6), 4: (6-5), 5: (5-4), 6: (4-3), 7: (3-2) and 8: (2-1) from the inside to the outside in the radial direction, and the content of manganese element in the radial coating layer increases successively. As the content of manganese element increases, its voltage platform also increases, while the discharge performance decreases successively. Through the coating rule of the embodiment of the present application, the contact path between the material and the electrolyte is shortened successively, and the ion transport migration path is shortened successively, thereby better balancing the discharge performance and compaction density of the lithium manganese iron phosphate material.

[0037] In some embodiments, in the eight lithium manganese iron phosphate coating layers, the particle sizes of the lithium manganese iron phosphate particles are 320-360 nm, 280-320 nm, 240-280 nm, 200-240 nm, 160-200 nm, 120-240 nm, 80-120 nm, and 50-80 nm from the inside to the outside in the radial direction.

[0038] In the embodiment of the present application, since the content of manganese in the radial coating layer increases successively, the voltage platform also increases as the manganese content increases. The coating form in which the particle size decreases from the inside to the outside along the radial direction is adopted, which is beneficial to further improve the discharge efficiency of the material and improve the compaction density of the composite material.

[0039] In some embodiments, in the polyphosphate positive electrode material, the first composite material, the second composite material and the third composite material all contain eight lithium iron manganese phosphate coating layers, and the grading of single-core multi-shell lithium iron manganese phosphate composite materials of the same structure but different sizes is more conducive to improving the stability of the polyphosphate positive electrode material.

[0040] In some embodiments, in the first composite material, the particle size of the inner core is 360-1600 nm, the molar ratio of manganese element to iron element is 1:(9-8), 2:(8-7), 3:(7-6), 4:(6-5), 5:(5-4), 6:(4-3), 7:(3-2) and 8:(2-1), and the thickness of the lithium manganese iron phosphate coating layer is 320-360 nm, 280-320 nm, 240-280 nm, 200-240 nm, 160-200 nm, 120-1600 nm, 80-2400 nm and 50-800 nm respectively. That is, the thickness of the lithium manganese iron phosphate coating layer with a molar ratio of manganese to iron of 1:(9-8) is 320-360nm; the thickness of the lithium manganese iron phosphate coating layer with a molar ratio of manganese to iron of 2:(8-7) is 280-320nm; the thickness of the lithium manganese iron phosphate coating layer with a molar ratio of manganese to iron of 3:(7-6) is 240-280nm; the thickness of the lithium manganese iron phosphate coating layer with a molar ratio of manganese to iron of 4:(6-5) is 200-240nm The thickness of the lithium manganese iron phosphate coating layer with a molar ratio of manganese to iron of 5:(5-4) is 160-200nm; the thickness of the lithium manganese iron phosphate coating layer with a molar ratio of manganese to iron of 6:(4-3) is 120-1600nm; the thickness of the lithium manganese iron phosphate coating layer with a molar ratio of manganese to iron of 7:(3-2) is 80-2400nm; the thickness of the lithium manganese iron phosphate coating layer with a molar ratio of manganese to iron of 8:(2-1) is 50-800nm. The ratio of manganese to iron in the core of the first composite material, the ratio of manganese to iron in each coating layer, and the coating thickness make the first composite material have a suitable particle size, which is conducive to improving the comprehensive properties of the polyphosphate positive electrode material, such as energy density, conductivity, and compaction density.

[0041] In some embodiments, in the second composite material, the particle size of the inner core is 720-3200 nm, the molar ratio of manganese element to iron element is 1: (9-8), 2: (8-7), 3: (7-6), 4: (6-5), 5: (5-4), 6: (4-3), 7: (3-2) and 8: (2-1), and the thickness of the lithium manganese iron phosphate coating layer is 640-720 nm, 560-640 nm, 480-560 nm, 400-480 nm, 320-400 nm, 240-3200 nm, 160-4800 and 100-1600 nm respectively. That is, in the second composite material, the molar ratio of manganese element to iron element in multiple lithium manganese iron phosphate coating layers is 1: (9-8), 2: (8-7), 3: (7-6), 4: (6-5), 5: (5-4), 6: (4-3), 7: (3-2) and 8: (2-1) from the inside to the outside in the radial direction, and the thickness of each coating layer is 640-720nm, 560-640nm, 480-560nm, 400-480nm, 320-400nm, 240-3200nm, 160-4800, 100-1600nm from the inside to the outside in the radial direction. The structure and material of the second composite material of the embodiment of the present application are the same as those of the first composite material, only the kernel particle size and the thickness of each coating layer are enlarged by a certain proportion, so that the overall particle size of the second composite material is increased, so that the second composite material is also conducive to improving the comprehensive performance of the energy density, electrical conductivity and compaction density of the polyphosphate positive electrode material.

[0042] In some embodiments, in the third composite material, the particle size of the inner core is 1440-6400 nm, the molar ratio of manganese element to iron element is 1: (9-8), 2: (8-7), 3: (7-6), 4: (6-5), 5: (5-4), 6: (4-3), 7: (3-2) and 8: (2-1), and the thickness of the lithium manganese iron phosphate coating layer is 400-480 nm, 360-440 nm, 320-400 nm, 280-360 nm, 240-320 nm, 200-6240 nm, 400-16000 nm, and 240--8000 nm, respectively. That is, in the third composite material, the molar ratio of manganese element to iron element in multiple lithium manganese iron phosphate coating layers is 1: (9-8), 2: (8-7), 3: (7-6), 4: (6-5), 5: (5-4), 6: (4-3), 7: (3-2) and 8: (2-1) from the inside to the outside in the radial direction, and the thickness of each coating layer is 1280-1440nm, 1120-1280nm, 960-1120nm, 800-960nm, 640-800nm, 480-6400nm, 320-9600nm, 200-3200nm from the inside to the outside in the radial direction. The structure and material of the third composite material of the embodiment of the present application are the same as those of the first composite material, only the kernel particle size and the thickness of each coating layer are enlarged by a certain proportion, so that the overall particle size of the third composite material is increased, so that the third composite material is also conducive to improving the comprehensive performance of the energy density, electrical conductivity and compaction density of the polyphosphate positive electrode material.

[0043] In some embodiments, in the single-core multi-shell lithium manganese iron phosphate composite material, the mass percentage of the carbon coating layer is 1 to 3wt%. In the composite material, the mass percentage of the carbon coating layer is conducive to regulating the size of the single-core multi-shell lithium manganese iron phosphate composite material, preventing it from agglomerating to form large particles during subsequent processing, and effectively improving the conductivity of the single-core multi-shell lithium manganese iron phosphate composite material, thereby improving the electrochemical performance of the composite material. If the content of the carbon coating layer is too low, the coating is incomplete, which is not conducive to improving the structural and performance stability of the single-core multi-shell lithium manganese iron phosphate composite material; if the content of the carbon coating layer is too high, the carbon coating layer is excessively coated on the single-core multi-shell lithium manganese iron phosphate composite material, which is not conducive to the performance of the material, and will also reduce the content of lithium manganese iron phosphate material in the composite material, and reduce the energy density of the material. In some specific embodiments, in the single-core multi-shell lithium manganese iron phosphate composite material, the mass percentage of the carbon coating layer includes but is not limited to 1wt%, 2wt%, 3wt%, etc. In some embodiments, the thickness of the carbon coating layer is 1-3 nm, which is conducive to forming a complete coating layer while preventing the carbon coating layer from being too thick to reduce the energy density of the composite material.

[0044] In some embodiments, the lithium iron manganese phosphate particles are selected from carbon-coated lithium iron manganese phosphate particles, wherein the mass percentage of the carbon material is 1 to 3wt%. This content of carbon material is beneficial to improving the conductivity of the lithium iron manganese phosphate material, and can completely coat the lithium iron manganese phosphate particles, prevent the lithium iron manganese phosphate from being oxidized, inhibit particle growth, and improve the structural stability of the lithium iron manganese phosphate particles. If the content of the carbon material is too high, the carbon coating layer will coat the lithium iron manganese phosphate particles too tightly, which will reduce the structural stability of the material during the secondary sintering process, and is not conducive to the performance of the material, and will reduce the content of the lithium iron manganese phosphate material in the composite material, reducing the energy density of the material. If the content of the carbon material is too low, the coating is incomplete, which is not conducive to improving the structural and performance stability of the lithium iron manganese phosphate particles. In some embodiments, in the lithium iron manganese phosphate particles, the mass percentage of the carbon material includes but is not limited to 1wt%, 2wt%, 3wt%, etc.

[0045] In some embodiments, the core is selected from carbon-coated lithium iron phosphate or carbon-coated lithium iron manganese phosphate, wherein the mass percentage of carbon material is 1 to 3wt%. This content of carbon material is beneficial to improving the conductivity of lithium iron phosphate materials, and can completely coat lithium iron phosphate particles to prevent lithium iron phosphate from being oxidized, inhibit particle growth, and improve the structural stability of lithium iron phosphate particles. If the content of carbon material is too low, the coating is incomplete, which is not conducive to improving the structural and performance stability of the material; if the content of carbon material is too high, it is not conducive to the performance of the material and will also reduce the energy density of the material. In some embodiments, the mass percentage of carbon material in the lithium iron phosphate or lithium iron manganese phosphate core includes but is not limited to 1wt%, 2wt%, 3wt%, etc.

[0046] The polyphosphate positive electrode material of the present application embodiment can be prepared by the following embodiment method.

[0047] As attached Figure 1 As shown, the second aspect of the embodiment of the present application provides a method for preparing a polyphosphate positive electrode material, comprising the following steps:

[0048] S10. preparing lithium iron phosphate particles and lithium manganese iron phosphate particles with different manganese to iron ratios, respectively; wherein the higher the manganese content in the lithium manganese iron phosphate particles, the smaller the particle size;

[0049] S20. With lithium iron phosphate or lithium iron manganese phosphate particles as the core, lithium iron manganese phosphate particles with different manganese to iron ratios are coated on the outer surface of the core in order according to the rule that the manganese content increases radially from the inside to the outside, to form multiple lithium iron manganese phosphate coating layers;

[0050] S30. Preparing a carbon coating layer on the surface of the outermost lithium manganese iron phosphate coating layer to obtain a single-core multi-shell lithium manganese iron phosphate composite material;

[0051] S40. The same method is used to prepare a number of different sizes of single-core multi-shell lithium manganese iron phosphate composite materials, a number of single-core multi-shell lithium manganese iron phosphate composite materials in the same or different number of lithium manganese iron phosphate coating layer; a number of single-core multi-shell lithium manganese iron phosphate composite materials having different core particle sizes, the thickness of each coating layer is different;

[0052] S50. Mixing a plurality of single-core multi-shell lithium manganese iron phosphate composite materials to obtain a polyphosphate positive electrode material.

[0053] The preparation method of the polyphosphate positive electrode material provided in the second aspect of the embodiment of the present application, after preparing lithium iron phosphate particles and lithium iron manganese phosphate particles with different manganese-iron ratios, lithium iron phosphate or lithium iron manganese phosphate particles are used as the core, and the lithium iron manganese phosphate particles are coated on the outer surface of the core in sequence according to the rule that the manganese content increases radially from the inside to the outside to form multiple lithium iron manganese phosphate coating layers. Then a carbon coating layer is prepared on the outermost side to obtain a single-core multi-shell lithium iron manganese phosphate composite material. Then, a number of single-core multi-shell lithium iron manganese phosphate composite materials of different sizes are prepared in the same way, and the number of layers of lithium iron manganese phosphate coating layers in a number of single-core multi-shell lithium iron manganese phosphate composite materials is the same or different; the core particle size of a number of single-core multi-shell lithium iron manganese phosphate composite materials is different, and the thickness of each coating layer is different. Then, a number of composite materials with the same or similar structure and different sizes are mixed to obtain a polyphosphate positive electrode material. The preparation method of the polyphosphate positive electrode material in the embodiment of the present application is simple in process, and only two sinterings are required to obtain a finished product, the production line conversion difficulty is low, the operation difficulty is low, and it is easy to realize industrial large-scale production and application. The prepared polyphosphate positive electrode material has high conductivity, high energy density, high compaction density and excellent comprehensive electrochemical performance through the synergistic effect of several single-core multi-shell lithium manganese iron phosphate composite materials with the same or similar structures but different sizes.

[0054] In some embodiments, in the above step S10, the method for preparing lithium iron phosphate particles includes but is not limited to mixing an iron source, a lithium source, a phosphorus source and a carbon source and then sintering the mixture to obtain carbon-coated lithium iron phosphate single crystal particles. In some embodiments, the carbon source includes but is not limited to at least one of sucrose, glucose, oxalic acid, salicylic acid, citric acid, tartaric acid, malic acid, glycine, ethylenediaminetetraacetic acid, and succinic acid, which can be converted into gaseous hydrocarbons during high-temperature sintering and can be deposited on the surface of lithium iron phosphate particles to form a carbon coating layer. In some specific embodiments, after mixing iron phosphate and lithium carbonate, sintering at a temperature of 650 to 750 ° C for 8 to 10 hours can obtain carbon-coated lithium iron phosphate particles. The particle size of the lithium iron phosphate particles in the above embodiment of the present application can be reduced by the sintering temperature and time conditions, and the sintering temperature and sintering time can be reduced, which can flexibly meet the requirements of the preparation of the first composite material, the second composite material and the third composite material for the core particle size.

[0055] In some embodiments, the added mass percentage of carbon material is 1-3wt%. This content of carbon material is beneficial to improving the conductivity of the lithium iron phosphate material, and can completely cover the lithium iron phosphate particles, prevent the lithium iron phosphate from being oxidized, inhibit particle growth, and improve the structural stability of the lithium iron phosphate particles.

[0056] In some embodiments, the preparation of lithium iron manganese phosphate particles with different manganese to iron ratios includes the steps of: mixing the manganese source, iron source, lithium source and carbon source and sintering them respectively according to the molar ratio of the manganese source to the iron source of 1: (9-8), 2: (8-7), 3: (7-6), 4: (6-5), 5: (5-4), 6: (4-3), 7: (3-2) or 8: (2-1) to obtain carbon-coated lithium iron manganese phosphate particles with different manganese to iron ratios. In some embodiments, the manganese source is manganese phosphate and the iron source is iron phosphate, which can provide both manganese and iron elements and a phosphorus source. In some embodiments, the total molar amount of the manganese source and the iron source is in a molar ratio of 1:1:1 to the lithium source and the phosphorus source. In some embodiments, the carbon source includes but is not limited to at least one of sucrose, glucose, oxalic acid, salicylic acid, citric acid, tartaric acid, malic acid, glycine, ethylenediaminetetraacetic acid, and succinic acid. These carbon sources can be converted into gaseous hydrocarbons during high-temperature sintering and can be deposited on the surface of lithium manganese iron phosphate particles to form a carbon coating layer.

[0057] In some embodiments, when preparing lithium iron manganese phosphate particles with different manganese to iron ratios, the higher the manganese content, the lower the sintering temperature. When the molar ratio of manganese source to iron source is 1: (9-8), 2: (8-7), 3: (7-6), 4: (6-5), 5: (5-4), 6: (4-3), 7: (3-2) or 8: (2-1), the corresponding sintering treatment temperatures are 560-600° C., 530-560° C., 500-530° C., 470-500° C., 440-470° C., 410-440° C., 380-410° C., and 350-380° C., respectively. The sintering time includes but is not limited to 8-24 hours. That is, when the molar ratio of the manganese source to the iron source is 1: (9-8), the manganese source, iron source, lithium source, phosphorus source and carbon source are mixed and sintered at a temperature of 560-600°C to prepare carbon-coated lithium iron manganese phosphate particles with a manganese-iron ratio of 1: (9-8). When the molar ratio of the manganese source to the iron source is 2: (8-7), the manganese source, iron source, lithium source, phosphorus source and carbon source are mixed and sintered at a temperature of 530-560°C to prepare carbon-coated lithium iron manganese phosphate particles with a manganese-iron ratio of 2: (8-7). When the molar ratio of the manganese source to the iron source is 3: (7-6), the manganese source, iron source, lithium source, phosphorus source and carbon source are mixed and sintered at a temperature of 500-530°C to prepare carbon-coated lithium iron manganese phosphate particles with a manganese-iron ratio of 3: (7-6). When the molar ratio of the manganese source to the iron source is 4:(6-5), the manganese source, iron source, lithium source, phosphorus source and carbon source are mixed and sintered at a temperature of 470-500°C to prepare carbon-coated lithium iron manganese phosphate particles with a manganese-iron ratio of 4:(6-5). When the molar ratio of the manganese source to the iron source is 5:(5-4), the manganese source, iron source, lithium source, phosphorus source and carbon source are mixed and sintered at a temperature of 440-470°C to prepare carbon-coated lithium iron manganese phosphate particles with a manganese-iron ratio of 5:(5-4). When the molar ratio of the manganese source to the iron source is 6:(4-3), the manganese source, iron source, lithium source, phosphorus source and carbon source are mixed and sintered at a temperature of 410-440°C to prepare carbon-coated lithium iron manganese phosphate particles with a manganese-iron ratio of 6:(4-3). When the molar ratio of the manganese source to the iron source is 7:(3-2), the manganese source, iron source, lithium source, phosphorus source and carbon source are mixed and sintered at a temperature of 380-410°C to prepare carbon-coated lithium iron manganese phosphate particles with a manganese-iron ratio of 7:(3-2). When the molar ratio of the manganese source to the iron source is 8:(2-1), the manganese source, iron source, lithium source, phosphorus source and carbon source are mixed and sintered at a temperature of 350-380°C to prepare carbon-coated lithium iron manganese phosphate particles with a manganese-iron ratio of 8:(2-1). The higher the sintering treatment temperature in the above-mentioned embodiment of the present application, the larger the particle size of the lithium iron manganese phosphate particles prepared, and the lower the temperature, the smaller the particle size of the lithium iron manganese phosphate particles prepared. In the lithium iron manganese phosphate particles, the higher the manganese content, the higher the voltage platform of the material, and the worse the discharge performance.Therefore, in the embodiment of the present application, as the manganese content in the lithium manganese iron phosphate particles increases, the sintering temperature is gradually reduced, so that the particle size of the prepared lithium manganese iron phosphate particles decreases step by step as the manganese content increases, thereby shortening the ion migration transmission path.

[0058] In some embodiments, the added mass percentage of carbon material is 1 to 3 wt %. This content of carbon material is beneficial to improving the conductivity of the lithium iron manganese phosphate material, and can completely cover the lithium iron manganese phosphate particles, prevent the lithium iron manganese phosphate from being oxidized, inhibit particle growth, and improve the structural stability of the lithium iron manganese phosphate particles.

[0059] In some embodiments, in the above step S20, lithium iron phosphate or lithium iron manganese phosphate particles are used as the inner core, and lithium iron manganese phosphate particles with different manganese-iron ratios are made into slurries respectively, and then they are coated on the inner core surface in sequence according to the rule that the manganese content increases radially from the inside to the outside, to form multiple carbon-coated lithium iron manganese phosphate coating layers. In some specific embodiments, lithium iron phosphate particles are used as the inner core, and the first coating layer from the inside to the outside in the radial direction is a lithium iron manganese phosphate coating layer with a manganese-iron ratio of 1: (9-8), the second coating layer is a lithium iron manganese phosphate coating layer with a manganese-iron ratio of 2: (8-7), the third coating layer is a lithium iron manganese phosphate coating layer with a manganese-iron ratio of 3: (7-6), the fourth coating layer is a lithium iron manganese phosphate coating layer with a manganese-iron ratio of 4: (6-5), the fifth coating layer is a lithium iron manganese phosphate coating layer with a manganese-iron ratio of 5: (5-4), the sixth coating layer is a lithium iron manganese phosphate coating layer with a manganese-iron ratio of 6: (4-3), the seventh coating layer is a lithium iron manganese phosphate coating layer with a manganese-iron ratio of 7: (3-2), and the eighth coating layer is a lithium iron manganese phosphate coating layer with a manganese-iron ratio of 8: (2-1).

[0060] In some embodiments, in the above step S30, the step of preparing a carbon coating layer on the surface of the outermost lithium manganese iron phosphate coating layer includes but is not limited to mixing the coating material having multiple lithium manganese iron phosphate coating layers with the carbon material, and then sintering the coating material, and forming a carbon material coating layer on the outer surface of the coating material during the secondary sintering process. In some embodiments, the carbon source includes but is not limited to at least one of sucrose, glucose, oxalic acid, salicylic acid, citric acid, tartaric acid, malic acid, glycine, ethylenediaminetetraacetic acid, and succinic acid, and these carbon sources can be converted into gaseous hydrocarbons during the high-temperature sintering process, and can be deposited on the surface of the material to form a carbon coating layer.

[0061] In some embodiments, the added mass percentage of carbon material is 1 to 3wt%; in the composite material, the carbon coating layer of this mass percentage is conducive to regulating the size of the single-core multi-shell lithium manganese iron phosphate composite material, preventing it from agglomerating to form large particles during subsequent processing, and effectively improving the conductivity of the single-core multi-shell lithium manganese iron phosphate composite material, thereby improving the electrochemical performance of the composite material. If the content of the carbon coating layer is too low, the coating is incomplete, which is not conducive to improving the structural and performance stability of the single-core multi-shell lithium manganese iron phosphate composite material; if the content of the carbon coating layer is too high, the carbon coating layer is excessively coated on the single-core multi-shell lithium manganese iron phosphate composite material, which is not conducive to the performance of the material, and will also reduce the content of lithium manganese iron phosphate material in the composite material, reducing the energy density of the material. In some specific embodiments, in the single-core multi-shell lithium manganese iron phosphate composite material, the mass percentage of the carbon coating layer includes but is not limited to 1wt%, 2wt%, 3wt%, etc.

[0062] In some embodiments, in the above step S40, the step of preparing several single-core multi-shell lithium manganese iron phosphate composite materials of different sizes includes: preparing three single-core multi-shell lithium manganese iron phosphate composite materials of the same structure but different sizes, namely a first composite material, a second composite material and a third composite material.

[0063] In some embodiments, in the first composite material, the second composite material and the third composite material, the ratio of the core particle size is (1-1.05): (2-2.1): (4-4.2), and the ratio of the thickness of each coating layer is independently (1-1.05): (2-2.1): (4-4.2). That is, according to the ratio of the core particle size and the thickness of each coating layer of the first composite material to the second composite material is (1-1.05): (2-2.1), the core of the second composite material, multiple lithium iron manganese phosphate coating layers and carbon coating layers are prepared in sequence. According to the ratio of the core particle size and the thickness of each coating layer of the first composite material to the third composite material is (1-1.05): (4-4.2), the core of the third composite material, multiple lithium iron manganese phosphate coating layers and carbon coating layers are prepared in sequence. By using three composite materials with the same or similar structures but different sizes as the polyphosphate positive electrode materials, the small-sized composite materials can be filled in the gaps of the large-sized composite materials to form a graded distribution, which not only ensures the electrochemical properties of the polyphosphate positive electrode materials, but also helps to improve the overall compaction density of the polyphosphate positive electrode materials and improve the energy density of the polyphosphate positive electrode materials.

[0064] In some embodiments, in the above step S50, the step of mixing treatment includes: mixing the first composite material, the second composite material and the third composite material in a mass ratio of 1: (2-4): (5-7), and then performing powder grading in a ball mill to obtain a polyphosphate positive electrode material. The first composite material, the second composite material and the third composite material in the embodiment of the present application have a ratio of (1-1.05): (2-2.1): (4-4.2) of the kernel particle size and the thickness of each coating layer, and have the same or similar phase structure but different sizes, and are graded in a mass ratio of 1: (2-4): (5-7), so that there is a better grading relationship between the three sizes of composite materials, which is more conducive to improving the compaction density and electrochemical performance of the polyphosphate positive electrode material. In some specific embodiments, in the polyphosphate positive electrode material, the mass ratio of the first composite material, the second composite material and the third composite material includes but is not limited to 1:2:5, 1:2:6, 1:2:7, 1:3:5, 1:3:6, 1:3:7, 1:4:5, 1:4:6, 1:4:7, etc.

[0065] In some embodiments, in the first composite material, the second composite material and the third composite material, the mass ratios of the inner core, the lithium iron manganese phosphate coating layer with a manganese-iron ratio of 8:(2-1), the lithium iron manganese phosphate coating layer with a manganese-iron ratio of 7:(3-2), the lithium iron manganese phosphate coating layer with a manganese-iron ratio of 6:(4-3), the lithium iron manganese phosphate coating layer with a manganese-iron ratio of 5:(5-4), the lithium iron manganese phosphate coating layer with a manganese-iron ratio of 4:(6-5), the lithium iron manganese phosphate coating layer with a manganese-iron ratio of 3:(7-6), the lithium iron manganese phosphate coating layer with a manganese-iron ratio of 2:(8-7), and the lithium iron manganese phosphate coating layer with a manganese-iron ratio of 1:(9-8) are (1-10):(1-20):(3-13):1:1:1:1:1:1:1. The embodiment of the present application can adjust the ratio of the overall manganese element and iron element in the composite material and the multi-phosphate positive electrode material by adjusting the ratio of each lithium iron manganese phosphate coating layer. The inner core and the lithium iron manganese phosphate coating layer with different manganese and iron ratios form a coating layer according to the above ratio, so that the molar ratio of manganese element and iron element in the multi-phosphate positive electrode material is 6:4. This ratio is beneficial to simultaneously ensure the comprehensive performance of the multi-phosphate positive electrode material, such as conductivity, energy density, and compaction density.

[0066] A third aspect of an embodiment of the present application provides a secondary battery, wherein the positive electrode material of the secondary battery includes the above-mentioned polyphosphate positive electrode material, or includes the polyphosphate positive electrode material prepared by the above-mentioned method.

[0067] The secondary battery provided in the third aspect of the embodiment of the present application comprises the above-mentioned polyphosphate positive electrode material, which, through the synergistic effect of a number of single-core multi-shell lithium manganese iron phosphate composite materials of the same or similar structure but different sizes, makes the polyphosphate positive electrode material have high conductivity, high energy density, high compaction density, and excellent comprehensive electrochemical performance. Thus, the electrochemical performance of the secondary battery is improved.

[0068] In order to enable the above implementation details and operations of the present application to be clearly understood by those skilled in the art, as well as the polyphosphate positive electrode material and preparation method of the present application embodiment, and the significant embodiment of the improved performance of the secondary battery, the above technical scheme is illustrated by multiple embodiments below.

[0069] Example 1

[0070] A polyphosphate positive electrode material, the preparation of which comprises the following steps:

[0071] (1) Manganese phosphate and iron phosphate with a concentration higher than 99% are used as raw materials, and nine ratios of 8:2, 7:3, 6:4, 5:5, 4:6, 3:7, 2:8, 1:9, and 0:10 are prepared according to the molar ratio of manganese to iron, and the mass ratio of each ratio is 1:20:1:1:1:1:1:1:1:1; after mixing the manganese iron raw material of each ratio with lithium carbonate to form a raw material component, the raw material components of each ratio are mixed with a carbon source according to the rule of adding 2 g of carbon source per 100 g of material to obtain a mixed material. Mixtures with manganese-iron ratios of 0:10, 1:9, 2:8, 3:7, 4:6, 5:5, 6:4, 7:3, and 8:2 are calcined at 600°C, 560°C, 530°C, 500°C, 470°C, 440°C, 410°C, 380°C, and 350°C for 8h to obtain carbon-coated lithium iron phosphate or carbon-coated lithium manganese iron phosphate with manganese-iron ratios of 0:10, 1:9, 2:8, 3:7, 4:6, 5:5, 6:4, 7:3, and 8:2, respectively, and the corresponding particle sizes are 360-400nm, 320-360nm, 280-320nm, 240-280nm, 200-240nm, 160-200nm, 120-160nm, 80-120nm, and 50-80nm, respectively;

[0072] (2) Using carbon-coated lithium iron phosphate as the core, the synthesized carbon-coated lithium manganese iron phosphate with different ratios is made into slurry by sand milling technology. Then, multiple carbon-coated lithium manganese iron phosphate coating layers are formed on the surface of the core in order of manganese iron ratio from low to high to obtain the first coated particles.

[0073] (3) The first coated particles were mixed with a carbon source and calcined at 650° C. for 8 h to form a carbon coating layer, thereby obtaining a first composite material having a particle size of 3.33 to 4.41 μm; wherein the core particle size was 360 to 400 nm, the coating layer thickness of a manganese iron lithium ratio of 1:9 was 320 to 360 nm, the coating layer thickness of a manganese iron lithium ratio of 2:8 was 280 to 320 nm, the coating layer thickness of a manganese iron lithium ratio of 3:7 was 240 to 280 nm, and the coating layer thickness of a manganese iron lithium ratio of 4:8 was 250 to 280 nm. :6 has a coating thickness of 200-240nm, a coating thickness of 5:5 manganese iron lithium ratio of 160-200nm, a coating thickness of 6:4 manganese iron lithium ratio of 120-160nm, a coating thickness of 7:3 manganese iron lithium ratio of 1600-2400nm, a coating thickness of 8:2 manganese iron lithium ratio of 50-80nm, a carbon coating thickness of 1-3nm, and the content of carbon coating in the first composite material is 1-3wt%.

[0074] (4) The method of steps (2) and (3) is used to prepare a second composite material with the same structure, forming a core particle size and each coating layer size with different sizes, and the particle size is 6.66 to 8.82 microns; wherein the core particle size is 720 to 800 nm, the coating layer thickness of the manganese iron lithium ratio of 1:9 is 640 to 720 nm, the coating layer thickness of the manganese iron lithium ratio of 2:8 is 560 to 640 nm, the coating layer thickness of the manganese iron lithium ratio of 3:7 is 480 to 560 nm, and the manganese iron lithium ratio is 1:1. The coating thickness of the lithium ratio of 4:6 is 400-480nm, the coating thickness of the manganese iron lithium ratio of 5:5 is 320-400nm, the coating thickness of the manganese iron lithium ratio of 6:4 is 240-320nm, the coating thickness of the manganese iron lithium ratio of 7:3 is 3200-4800nm, the coating thickness of the manganese iron lithium ratio of 8:2 is 100-160nm, the thickness of the carbon coating layer is 1-3nm, and the content of the carbon coating layer in the second composite material is 1-3wt%.

[0075] (5) The method of steps (2) and (3) is used to prepare a third composite material having the same structure, with different core particle sizes and coating layer sizes, wherein the particle size is 13.32 to 17.64 microns; wherein the core particle size is 1440 to 1600 nm, the coating layer thickness of the manganese iron lithium ratio of 1:9 is 1280 to 1440 nm, the coating layer thickness of the manganese iron lithium ratio of 2:8 is 1180 to 1280 nm, and the coating layer thickness of the manganese iron lithium ratio of 3:7 is 960 to 1280 nm. nm, the coating thickness of the manganese iron lithium ratio of 4:6 is 800-960nm, the coating thickness of the manganese iron lithium ratio of 5:5 is 640-800nm, the coating thickness of the manganese iron lithium ratio of 6:4 is 480-640nm, the coating thickness of the manganese iron lithium ratio of 7:3 is 6400-9600nm, the coating thickness of the manganese iron lithium ratio of 8:2 is 200-320nm, the thickness of the carbon coating layer is 1-3nm, and the content of the carbon coating layer in the third composite material is 1-3wt%.

[0076] (6) After cooling the first composite material, the second composite material and the third composite material prepared in steps 3 to 5, they are crushed and sieved, and then the particles of the three sizes are mixed in a mass ratio of 1:3:6 for the first composite material, the second composite material and the third composite material, and then put into a ball mill for powder grading. After the grading, the materials are dried and packaged to obtain the final product, i.e., the polyphosphate positive electrode material. The molar ratio of manganese element to iron element in the polyphosphate positive electrode material is 6:4.

[0077] Example 2

[0078] A polyphosphate positive electrode material, which differs from Example 1 in that:

[0079] In step (1), nine ratios of manganese to iron are prepared according to the molar ratio of 8:2, 7:3, 6:4, 5:5, 4:6, 3:7, 2:8, 1:9 and 0:10, and the mass ratio of each ratio is 10:1:10:1:1:1:1:1:1:1.

[0080] Step (3) The first coated particles are mixed with a carbon source and then calcined at 650°C for 8 hours to form a carbon coating layer. The obtained first composite material has a particle size of 3.34 to 4.32 microns; wherein the core particle size is 360 to 400 nm, the coating layer thickness of the manganese iron lithium ratio of 1:9 is 320 to 360 nm, the coating layer thickness of the manganese iron lithium ratio of 2:8 is 280 to 320 nm, the coating layer thickness of the manganese iron lithium ratio of 3:7 is 240 to 280 nm, and the manganese iron lithium ratio is 2:8. The coating thickness of the manganese iron lithium ratio of 4:6 is 200-240nm, the coating thickness of the manganese iron lithium ratio of 5:5 is 160-200nm, the coating thickness of the manganese iron lithium ratio of 6:4 is 1200-1600nm, the coating thickness of the manganese iron lithium ratio of 7:3 is 80-120nm, the coating thickness of the manganese iron lithium ratio of 8:2 is 500-800nm, the thickness of the carbon coating layer is 1-3nm, and the content of the carbon coating layer in the first composite material is 1-3wt%.

[0081] Step (4) forms a second composite material with different core particle sizes and coating layer sizes, wherein the particle size is 6.68 to 8.64 microns; wherein the core particle size is 720 to 800 nm, the coating layer thickness of the manganese iron lithium ratio of 1:9 is 640 to 720 nm, the coating layer thickness of the manganese iron lithium ratio of 2:8 is 560 to 640 nm, the coating layer thickness of the manganese iron lithium ratio of 3:7 is 480 to 560 nm, and the coating layer thickness of the manganese iron lithium ratio of 4:6 is 100 to 150 nm. The coating thickness is 400-480nm, the coating thickness of the manganese iron lithium ratio of 5:5 is 320-400nm, the coating thickness of the manganese iron lithium ratio of 6:4 is 2400-3200nm, the coating thickness of the manganese iron lithium ratio of 7:3 is 160-240nm, the coating thickness of the manganese iron lithium ratio of 8:2 is 1000-1600nm, the thickness of the carbon coating layer is 1-3nm, and the content of the carbon coating layer in the second composite material is 1-3wt%.

[0082] Step (5) forms a third composite material with different core particle sizes and coating layer sizes, wherein the particle size is 13.36 to 17.28 microns; wherein the core particle size is 1440 to 1600 nm, the coating layer thickness of the manganese iron lithium ratio of 1:9 is 1280 to 1440 nm, the coating layer thickness of the manganese iron lithium ratio of 2:8 is 1180 to 1280 nm, the coating layer thickness of the manganese iron lithium ratio of 3:7 is 960 to 1280 nm, and the coating layer thickness of the manganese iron lithium ratio of 4:6 is 960 to 1280 nm. The coating layer thickness is 800-960nm, the coating layer thickness of the manganese iron lithium ratio of 5:5 is 640-800nm, the coating layer thickness of the manganese iron lithium ratio of 6:4 is 4800-6400nm, the coating layer thickness of the manganese iron lithium ratio of 7:3 is 320-480nm, the coating layer thickness of the manganese iron lithium ratio of 8:2 is 2000-3200nm, the thickness of the carbon coating layer is 1-3nm, and the content of the carbon coating layer in the third composite material is 1-3wt%.

[0083] Step (6) After cooling the first composite material, the second composite material and the third composite material prepared in steps 3 to 5, they are crushed and sieved, and then the particles of the three sizes are mixed in a mass ratio of 1:3:6 for the first composite material, the second composite material and the third composite material, and then put into a ball mill for powder grading. After the grading, the materials are dried and packaged to obtain the final product, i.e., the polyphosphate positive electrode material. The molar ratio of manganese element to iron element in the polyphosphate positive electrode material is 6:4.

[0084] Example 3

[0085] A polyphosphate positive electrode material, which differs from Example 1 in that:

[0086] In step (1), nine ratios of manganese to iron are prepared according to the molar ratio of 8:2, 7:3, 6:4, 5:5, 4:6, 3:7, 2:8, 1:9 and 0:10, and the mass ratio of each ratio is 6:8:6:1:1:1:1:1:1:1.

[0087] Step (3) The first coated particles are mixed with a carbon source and then calcined at 650°C for 8h to form a carbon coating layer to obtain a first composite material with a particle size of 3.34 to 4.32 microns; wherein the core particle size is 360 to 400nm, the coating layer thickness of the manganese iron lithium ratio of 1:9 is 320 to 360nm, the coating layer thickness of the manganese iron lithium ratio of 2:8 is 280 to 320nm, the coating layer thickness of the manganese iron lithium ratio of 3:7 is 240 to 280nm, and the manganese iron lithium ratio is 2:8. The coating thickness of the manganese iron lithium ratio of 4:6 is 200-240nm, the coating thickness of the manganese iron lithium ratio of 5:5 is 160-200nm, the coating thickness of the manganese iron lithium ratio of 6:4 is 720-960nm, the coating thickness of the manganese iron lithium ratio of 7:3 is 640-960nm, the coating thickness of the manganese iron lithium ratio of 8:2 is 300-480nm, the thickness of the carbon coating layer is 1-3nm, and the content of the carbon coating layer in the first composite material is 1-3wt%.

[0088] Step (4) adopts the method of step (2) and (3) to prepare a second composite material with the same structure, forming a core particle size and each coating layer size with different sizes, and the particle size is 6.68-8.64 microns; wherein the core particle size is 720-800nm, the coating layer thickness of the manganese iron lithium ratio of 1:9 is 640-720nm, the coating layer thickness of the manganese iron lithium ratio of 2:8 is 560-640nm, the coating layer thickness of the manganese iron lithium ratio of 3:7 is 480-560nm, and the manganese iron lithium ratio is 1:1. The coating thickness of the lithium ratio of 4:6 is 400-480nm, the coating thickness of the manganese iron lithium ratio of 5:5 is 320-400nm, the coating thickness of the manganese iron lithium ratio of 6:4 is 1440-1920nm, the coating thickness of the manganese iron lithium ratio of 7:3 is 1280-1920nm, the coating thickness of the manganese iron lithium ratio of 8:2 is 600-960nm, the thickness of the carbon coating layer is 1-3nm, and the content of the carbon coating layer in the second composite material is 1-3wt%.

[0089] Step (5) forms a third composite material with different core particle sizes and coating layer sizes, wherein the particle size is 13.36 to 17.28 microns; wherein the core particle size is 1440 to 1600 nm, the coating layer thickness of the manganese iron lithium ratio of 1:9 is 1280 to 1440 nm, the coating layer thickness of the manganese iron lithium ratio of 2:8 is 1180 to 1280 nm, the coating layer thickness of the manganese iron lithium ratio of 3:7 is 960 to 1280 nm, and the coating layer thickness of the manganese iron lithium ratio of 4:6 is 1180 to 1280 nm. The coating thickness is 800-960nm, the coating thickness of the manganese iron lithium ratio of 5:5 is 640-800nm, the coating thickness of the manganese iron lithium ratio of 6:4 is 2800-3840nm, the coating thickness of the manganese iron lithium ratio of 7:3 is 2560-3840nm, the coating thickness of the manganese iron lithium ratio of 8:2 is 1200-1920nm, the thickness of the carbon coating layer is 1-3nm, and the content of the carbon coating layer in the third composite material is 1-3wt%.

[0090] Step (6) After cooling the first composite material, the second composite material and the third composite material prepared in steps 3 to 5, they are crushed and sieved, and then the particles of the three sizes are mixed in a mass ratio of 1:3:6 for the first composite material, the second composite material and the third composite material, and then put into a ball mill for powder grading. After the grading, the materials are dried and packaged to obtain the final product, i.e., the polyphosphate positive electrode material. The molar ratio of manganese element to iron element in the polyphosphate positive electrode material is 6:4.

[0091] Example 4

[0092] A polyphosphate positive electrode material, which differs from Example 1 in that:

[0093] In step (1), four ratios of manganese to iron are prepared according to the molar ratio of 8:2, 7:3, 6:4 and 0:10, and the mass ratio of each ratio is 12:1:1:4.

[0094] The calcination temperature in step (3) is 650°C, and the first composite material obtained has a particle size of 3.32 to 4.32 microns; wherein the core particle size is 1440 to 1600 nm, the coating layer thickness of the manganese iron lithium ratio of 1:9 is 320 to 360 nm, the coating layer thickness of the manganese iron lithium ratio of 2:8 is 280 to 320 nm, the coating layer thickness of the manganese iron lithium ratio of 3:7 is 240 to 280 nm, and the coating layer thickness of the manganese iron lithium ratio of 4: The coating thickness of the manganese iron lithium ratio of 6 is 200-240nm, the coating thickness of the manganese iron lithium ratio of 5:5 is 160-200nm, the coating thickness of the manganese iron lithium ratio of 6:4 is 120-160nm, the coating thickness of the manganese iron lithium ratio of 7:3 is 80-120nm, the coating thickness of the manganese iron lithium ratio of 8:2 is 600-760nm, the thickness of the carbon coating layer is 1-3nm, and the content of the carbon coating layer in the first composite material is 1-3wt%.

[0095] Step (4) adopts the method of step (2) and (3) to prepare a second composite material with the same structure, forming a core particle size and each coating layer size with different sizes, and the particle size is 6.68-8.64 microns; wherein the core particle size is 2880-3200nm, the coating layer thickness of the manganese iron lithium ratio of 1:9 is 640-720nm, the coating layer thickness of the manganese iron lithium ratio of 2:8 is 560-640nm, and the coating layer thickness of the manganese iron lithium ratio of 3:7 is 480-560nm, The coating thickness of the manganese iron lithium ratio of 4:6 is 400-480nm, the coating thickness of the manganese iron lithium ratio of 5:5 is 320-400nm, the coating thickness of the manganese iron lithium ratio of 6:4 is 240-320nm, the coating thickness of the manganese iron lithium ratio of 7:3 is 160-240nm, the coating thickness of the manganese iron lithium ratio of 8:2 is 1200-1520nm, the thickness of the carbon coating layer is 1-3nm, and the content of the carbon coating layer in the second composite material is 1-3wt%.

[0096] Step (5) forms a third composite material with different core particle sizes and coating layer sizes, wherein the particle size is 13.36 to 17.28 microns; wherein the core particle size is 5760 to 6400 nm, the coating layer thickness of the manganese iron lithium ratio of 1:9 is 1280 to 1440 nm, the coating layer thickness of the manganese iron lithium ratio of 2:8 is 1180 to 1280 nm, the coating layer thickness of the manganese iron lithium ratio of 3:7 is 960 to 1280 nm, and the coating layer thickness of the manganese iron lithium ratio of 4:6 is 1180 to 1280 nm. The coating thickness is 800-960nm, the coating thickness of the manganese iron lithium ratio of 5:5 is 640-800nm, the coating thickness of the manganese iron lithium ratio of 6:4 is 480-640nm, the coating thickness of the manganese iron lithium ratio of 7:3 is 320-480nm, the coating thickness of the manganese iron lithium ratio of 8:2 is 2400-3040nm, the thickness of the carbon coating layer is 1-3nm, and the content of the carbon coating layer in the third composite material is 1-3wt%.

[0097] Step (6) After cooling the first composite material, the second composite material and the third composite material prepared in steps 3 to 5, they are crushed and sieved, and then the particles of the three sizes are mixed in a mass ratio of 1:3:6 for the first composite material, the second composite material and the third composite material, and then put into a ball mill for powder grading. After the grading, the materials are dried and packaged to obtain the final product, i.e., the polyphosphate positive electrode material. The molar ratio of manganese element to iron element in the polyphosphate positive electrode material is 6:4.

[0098] Example 5

[0099] A polyphosphate positive electrode material, which differs from Example 1 in that:

[0100] In step (1), four ratios of manganese to iron are prepared according to the molar ratio of 8:2, 7:3, 6:4 and 0:10, and the mass ratio of each ratio is 1:1:1:7.

[0101] The calcination temperature in step (3) is 650°C, and the first composite material obtained has a particle size of 3.97 to 4.57 microns; wherein the core particle size is 2520 to 2800 nm, the coating layer thickness of the manganese iron lithium ratio of 1:9 is 320 to 360 nm, the coating layer thickness of the manganese iron lithium ratio of 2:8 is 280 to 320 nm, the coating layer thickness of the manganese iron lithium ratio of 3:7 is 240 to 280 nm, and the coating layer thickness of the manganese iron lithium ratio of 4 is 240 to 280 nm. :6 has a coating thickness of 200-240nm, a coating thickness of 5:5 manganese iron lithium ratio of 160-200nm, a coating thickness of 6:4 manganese iron lithium ratio of 120-160nm, a coating thickness of 7:3 manganese iron lithium ratio of 80-120nm, a coating thickness of 8:2 manganese iron lithium ratio of 50-80nm, a carbon coating thickness of 1-3nm, and the content of carbon coating in the first composite material is 1-3wt%.

[0102] Step (4) adopts the method of step (2) and (3) to prepare a second composite material with the same structure, forming a core particle size and each coating layer size with different sizes, and the particle size is 7.94-9.14 microns; wherein the core particle size is 5040-5600nm, the coating layer thickness of the manganese iron lithium ratio of 1:9 is 640-720nm, the coating layer thickness of the manganese iron lithium ratio of 2:8 is 560-640nm, and the coating layer thickness of the manganese iron lithium ratio of 3:7 is 480-560nm The coating thickness of the manganese iron lithium ratio of 4:6 is 400-480nm, the coating thickness of the manganese iron lithium ratio of 5:5 is 320-400nm, the coating thickness of the manganese iron lithium ratio of 6:4 is 240-320nm, the coating thickness of the manganese iron lithium ratio of 7:3 is 160-240nm, the coating thickness of the manganese iron lithium ratio of 8:2 is 100-160nm, the thickness of the carbon coating layer is 1-3nm, and the content of the carbon coating layer in the second composite material is 1-3wt%.

[0103] Step (5) forms a third composite material with different core particle sizes and coating layer sizes, wherein the particle size is 15.88 to 18.28 microns; wherein the core particle size is 10080 to 11200 nm, the coating layer thickness of the manganese iron lithium ratio of 1:9 is 1280 to 1440 nm, the coating layer thickness of the manganese iron lithium ratio of 2:8 is 1180 to 1280 nm, the coating layer thickness of the manganese iron lithium ratio of 3:7 is 960 to 1280 nm, and the coating layer thickness of the manganese iron lithium ratio of 4 is 10080 to 11200 nm. The coating thickness of the manganese iron lithium ratio of 5:6 is 800-960nm, the coating thickness of the manganese iron lithium ratio of 5:5 is 640-800nm, the coating thickness of the manganese iron lithium ratio of 6:4 is 480-640nm, the coating thickness of the manganese iron lithium ratio of 7:3 is 320-480nm, the coating thickness of the manganese iron lithium ratio of 8:2 is 200-320nm, the thickness of the carbon coating layer is 1-3nm, and the content of the carbon coating layer in the third composite material is 1-3wt%.

[0104] Step (6) After cooling the first composite material, the second composite material and the third composite material prepared in steps 3 to 5, the first composite material, the second composite material and the third composite material are crushed and sieved, and then the particles of the three sizes are mixed in a mass ratio of 1:3:6 for the first composite material, the second composite material and the third composite material, and then put into a ball mill for powder grading. After the grading, the materials are dried and packaged to obtain the final product, i.e., the polyphosphate positive electrode material. The molar ratio of manganese element to iron element in the polyphosphate positive electrode material is 2.4:7.6.

[0105] Comparative Example 1

[0106] A polyphosphate positive electrode material, the preparation of which comprises the following steps:

[0107] (1) Manganese phosphate and iron phosphate with a concentration higher than 99% are used as raw materials, and nine ratios of 8:2, 7:3, 6:4, 5:5, 4:6, 3:7, 2:8, 1:9, and 0:10 are prepared according to the molar ratio of manganese to iron, and the mass ratio of each ratio is 1:20:13:1:1:1:1:1:1:1; after mixing the manganese iron raw material of each ratio with lithium carbonate to form a raw material component, the raw material components of each ratio are mixed with a carbon source according to the rule of adding 2 g of carbon source per 100 g of material to obtain a mixed material. Mixtures with manganese-iron ratios of 0:10, 1:9, 2:8, 3:7, 4:6, 5:5, 6:4, 7:3 and 8:2 are calcined at 600°C, 570°C, 530°C, 500°C, 470°C, 440°C, 410°C, 380°C and 350°C for 8h, respectively, to obtain carbon-coated lithium iron phosphate or carbon-coated lithium manganese iron phosphate with manganese-iron ratios of 0:10, 1:9, 2:8, 3:7, 4:6, 5:5, 6:4, 7:3 and 8:2, and the corresponding particle sizes are 320-440nm, 280-360nm, 240-320nm, 200-300nm, 160-280nm, 120-240nm, 80-200nm and 50-160nm, respectively.

[0108] (2) Using carbon-coated lithium iron phosphate as the core, the synthesized carbon-coated lithium manganese iron phosphate with different ratios is made into slurry by sand milling technology. Then, multiple carbon-coated lithium manganese iron phosphate coating layers are formed on the surface of the core in order of manganese iron ratio from low to high to obtain the first coated particles.

[0109] (3) The first coated particles were mixed with 2 wt % of a carbon source and calcined at 650° C. for 8 h to form a carbon coating layer, thereby obtaining a first composite material having a particle size of 20 to 30 μm; wherein the core particle size was 360 to 400 nm, the coating layer thickness was 320 to 360 nm at a manganese iron lithium ratio of 1:9, the coating layer thickness was 280 to 320 nm at a manganese iron lithium ratio of 2:8, and the coating layer thickness was 240 to 350 nm at a manganese iron lithium ratio of 3:7. 280nm, the coating thickness of the manganese iron lithium ratio of 4:6 is 200-240nm, the coating thickness of the manganese iron lithium ratio of 5:5 is 160-200nm, the coating thickness of the manganese iron lithium ratio of 6:4 is 3120-4160nm, the coating thickness of the manganese iron lithium ratio of 7:3 is 6400-9600nm, the coating thickness of the manganese iron lithium ratio of 8:2 is 100-160nm, and the thickness of the carbon coating layer is 1-3nm. After the prepared first composite material is cooled, it is crushed and sieved, and the first composite material is used alone as a polyphosphate positive electrode material.

[0110] Comparative Example 2

[0111] A polyphosphate positive electrode material, which differs from Example 1 in that:

[0112] In step (2), multiple carbon-coated lithium manganese iron phosphate coating layers are formed by coating the surface of the inner core in order of manganese iron ratio from high to low.

[0113] In order to verify the progress of the embodiments of the present application, the finished products of the polyphosphate positive electrode materials prepared in the embodiments and comparative examples were subjected to powder compression test and electrical performance test respectively:

[0114] 1. Powder compression test: 1 g of the finished product of the polyphosphate positive electrode material of each embodiment and comparative example was weighed, and the tested compaction density at a pressure of 10 MPa (via a 3T pressure sensor) was shown in Table 1.

[0115] Table 1

[0116]

[0117]

[0118] 2. Battery performance test: Using the polyphosphate positive electrode material particles provided in the above embodiments and comparative examples, assemble the battery as follows:

[0119] Preparation of positive electrode sheet: Mix the polyphosphate positive electrode material, SP (conductive carbon black), PVDF (polyvinylidene fluoride) and NMP (N-methylpyrrolidone) in a mass ratio of 93.5:2.5:4:100 with a ball mill mixer for 2 hours to obtain a positive electrode slurry; add the prepared positive electrode slurry to the aluminum foil, scrape it evenly with a scraper, dry it at 130°C, and then roll it to obtain a positive electrode sheet.

[0120] Battery assembly process: The prepared positive electrode is attached to the positive electrode metal shell with conductive adhesive, a metal lithium sheet is used as the negative electrode, a Celgard 2400 microporous membrane is used as the separator, and a 1.0 mol / L LiPF6 solution is used as the electrolyte. The solvent of the electrolyte is a mixture of ethylene carbonate (EC), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC) in a volume ratio of 1:1:1. The button batteries are assembled in a glove box.

[0121] The electrochemical performance of the button cell was tested using a LAND electrochemical tester, with a charge termination voltage of 4.2 V and a discharge termination voltage of 2.0 V. The test results are shown in Table 2 below.

[0122] Table 2

[0123]

[0124]

[0125] It can be seen from the above test results that the polyphosphate positive electrode material prepared in the embodiment of the present application has excellent electrochemical properties such as excellent conductivity, energy density and compaction density through the synergistic effect of three different sizes of single-core multi-shell lithium manganese iron phosphate composite materials. When the comparative example 1 only uses one size of single-core multi-shell lithium manganese iron phosphate composite material as the polyphosphate positive electrode material, the compaction is lower than the grading, and there is no obvious difference in electrical properties. When the manganese content of the lithium manganese iron phosphate coating layer of the composite material in the polyphosphate positive electrode material of comparative example 2 decreases radially from the inside to the outside, the electrical properties are very poor, and the high manganese particles inside the particles are completely unable to release electrical properties. In addition, the manganese-iron ratio in the polyphosphate positive electrode material of Example 5 is 2.4 to 7.6, and its comprehensive electrochemical performance is lower than that of Examples 1 to 4 with a manganese-iron ratio of 6:4.

[0126] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.

Claims

1. A polyphosphate positive electrode material, characterized in that: The polyphosphate positive electrode material includes several single-core multi-shell lithium iron manganese phosphate composite materials; the single-core multi-shell lithium iron manganese phosphate composite material includes a lithium iron phosphate or lithium iron manganese phosphate core, a plurality of lithium iron manganese phosphate coating layers coated on the outer surface of the core, and a carbon coating layer coated on the outermost layer of the single-core multi-shell lithium iron manganese phosphate composite material; the lithium iron manganese phosphate coating layer includes lithium iron manganese phosphate particles; in the plurality of lithium iron manganese phosphate coating layers, the particle size of the lithium iron manganese phosphate particles decreases radially from the inside to the outside; the manganese content of the lithium iron manganese phosphate particles in the plurality of lithium iron manganese phosphate coating layers increases radially from the inside to the outside; the number of layers of the lithium iron manganese phosphate coating layers in several of the single-core multi-shell lithium iron manganese phosphate composite materials is the same or different; the core particle size of several of the single-core multi-shell lithium iron manganese phosphate composite materials is different, and the thickness of each coating layer is different.

2. The polyphosphate positive electrode material according to claim 1, characterized in that The polyphosphate positive electrode material includes three single-core multi-shell lithium manganese iron phosphate composite materials with the same structure but different sizes, namely a first composite material, a second composite material and a third composite material.

3. The polyphosphate positive electrode material according to claim 2, characterized in that: In the first composite material, the second composite material and the third composite material, the ratio of the core particle size is (1~1.05):(2~2.1):(4~4.2), and the ratio of the thickness of each coating layer is (1~1.05):(2~2.1):(4~4.2).

4. The polyphosphate positive electrode material according to claim 3, characterized in that: In the polyphosphate positive electrode material, the mass ratio of the first composite material, the second composite material and the third composite material is 1:(2-4):(5-7); And / or, the ratio of the particle sizes of the first composite material, the second composite material and the third composite material is (1.8-8):(3-16):(7-32).

5. The polyphosphate positive electrode material according to claim 4, characterized in that: The molar ratio of manganese to iron in the polyphosphate positive electrode material is 6:4; And / or, the molar ratio of manganese element to iron element in the core is (0-1):(2-9); And / or, the molar ratio of manganese element to iron element in the different lithium manganese iron phosphate coating layers is (1-9): (9-1).

6. The polyphosphate positive electrode material according to claim 5, characterized in that: The polyphosphate positive electrode material includes at least one of the single-core multi-shell lithium manganese iron phosphate composite materials comprising eight lithium manganese iron phosphate coating layers, wherein the molar ratios of manganese element to iron element in the eight lithium manganese iron phosphate coating layers are 1: (9-8), 2: (8-7), 3: (7-6), 4: (6-5), 5: (5-4), 6: (4-3), 7: (3-2) and 8: (2-1) from the inside to the outside along the radial direction.

7. The polyphosphate positive electrode material according to claim 6, characterized in that: In the eight lithium iron manganese phosphate coating layers, the particle sizes of the lithium iron manganese phosphate particles are 320~360nm, 280~320nm, 240~280nm, 200~240nm, 160~200nm, 120~240nm, 80~120nm, and 50~80nm from the inside to the outside in the radial direction.

8. The polyphosphate positive electrode material according to claim 7, characterized in that: In the polyphosphate positive electrode material, the first composite material, the second composite material and the third composite material all comprise eight lithium manganese iron phosphate coating layers; And / or, the particle size of the first composite material is 1.8-8 μm; the particle size of the second composite material is 3-16 μm; and the particle size of the third composite material is 7-32 μm.

9. The polyphosphate positive electrode material according to claim 8, characterized in that: In the first composite material, the particle size of the core is 360-1600 nm, the molar ratio of manganese element to iron element is 1: (9-8), 2: (8-7), 3: (7-6), 4: (6-5), 5: (5-4), 6: (4-3), 7: (3-2) and 8: (2-1), and the thickness of the lithium manganese iron phosphate coating layer is 320-360 nm, 280-320 nm, 240-280 nm, 200-240 nm, 160-200 nm, 120-1600 nm, 80-2400 nm and 50-800 nm respectively; And / or, in the second composite material, the particle size of the core is 720-3200 nm, the molar ratio of manganese element to iron element is 1: (9-8), 2: (8-7), 3: (7-6), 4: (6-5), 5: (5-4), 6: (4-3), 7: (3-2) and 8: (2-1), and the thickness of the lithium manganese iron phosphate coating layer is 640-720 nm, 560-640 nm, 480-560 nm, 400-480 nm, 320-400 nm, 240-3200 nm, 160-4800 and 100-1600 nm respectively; And / or, in the third composite material, the particle size of the core is 1440~6400nm, the molar ratio of manganese element to iron element is 1: (9~8), 2: (8~7), 3: (7~6), 4: (6~5), 5: (5~4), 6: (4~3), 7: (3~2) and 8: (2~1), and the thickness of the lithium manganese iron phosphate coating layer is 1280~1440nm, 1120~1280nm, 960~1120nm, 800~960nm, 640~800nm, 480~6400nm, 320~9600nm, and 200~3200nm respectively.

10. The polyphosphate positive electrode material according to any one of claims 1 to 9, characterized in that: In the single-core multi-shell lithium manganese iron phosphate composite material, the mass percentage of the carbon coating layer is 1-3wt%; And / or, the thickness of the carbon coating layer is 1-3 nm; And / or, the core is selected from carbon-coated lithium iron phosphate or carbon-coated lithium manganese iron phosphate, wherein the mass percentage of the carbon material is 1-3wt%; And / or, the lithium iron manganese phosphate particles are selected from carbon-coated lithium iron manganese phosphate particles, wherein the mass percentage of the carbon material is 1-3wt%.

11. A method for preparing a polyphosphate positive electrode material, characterized in that: The following steps are involved: preparing lithium iron phosphate particles and lithium manganese iron phosphate particles with different manganese to iron ratios respectively; wherein the higher the manganese content in the lithium manganese iron phosphate particles, the smaller the particle size; The lithium iron phosphate or lithium iron manganese phosphate particles are used as the inner core, and the lithium iron manganese phosphate particles with different manganese to iron ratios are coated on the outer surface of the inner core in sequence according to the rule that the manganese content increases radially from the inside to the outside, to form a plurality of lithium iron manganese phosphate coating layers; Preparing a carbon coating layer on the surface of the outermost lithium manganese iron phosphate coating layer to obtain a single-core multi-shell lithium manganese iron phosphate composite material; A plurality of single-core multi-shell lithium manganese iron phosphate composite materials of different sizes are prepared by the same method, wherein the number of layers of the lithium manganese iron phosphate coating layer in the plurality of single-core multi-shell lithium manganese iron phosphate composite materials is the same or different; the core particle size of the plurality of single-core multi-shell lithium manganese iron phosphate composite materials is different, and the thickness of each coating layer is different; A plurality of the single-core multi-shell lithium manganese iron phosphate composite materials are mixed to obtain a polyphosphate positive electrode material.

12. The method for preparing a polyphosphate positive electrode material according to claim 11, characterized in that: The step of preparing a plurality of single-core multi-shell lithium manganese iron phosphate composite materials of different sizes comprises: preparing three single-core multi-shell lithium manganese iron phosphate composite materials of the same structure but different sizes, namely a first composite material, a second composite material and a third composite material.

13. The method for preparing a polyphosphate positive electrode material according to claim 12, characterized in that: In the first composite material, the second composite material and the third composite material, the ratio of the core particle size is (1~1.05):(2~2.1):(4~4.2), and the ratio of the thickness of each coating layer is independently (1~1.05):(2~2.1):(4~4.2).

14. The method for preparing a polyphosphate positive electrode material according to claim 13, characterized in that: The preparation of the lithium iron manganese phosphate particles with different manganese-iron ratios comprises the steps of: mixing the manganese source, the iron source, the lithium source and the carbon source according to the molar ratio of the manganese source to the iron source of 1: (9-8), 2: (8-7), 3: (7-6), 4: (6-5), 5: (5-4), 6: (4-3), 7: (3-2) or 8: (2-1), and then sintering them respectively to obtain the lithium iron manganese phosphate particles with different manganese-iron ratios; And / or, the mixing step includes: mixing the first composite material, the second composite material and the third composite material in a mass ratio of 1:(2-4):(5-7), and then performing powder grading in a ball mill to obtain the polyphosphate positive electrode material.

15. The method for preparing a polyphosphate positive electrode material according to claim 14, characterized in that: When preparing the lithium iron manganese phosphate particles with different manganese to iron ratios, the higher the manganese content, the lower the sintering temperature. When the molar ratio of the manganese source to the iron source is 1: (9-8), 2: (8-7), 3: (7-6), 4: (6-5), 5: (5-4), 6: (4-3), 7: (3-2) or 8: (2-1), the corresponding sintering treatment temperatures are 560-600°C, 530-560°C, 500-530°C, 470-500°C, 440-470°C, 410-440°C, 380-410°C, and 350-380°C, respectively; And / or, in the first composite material, the second composite material and the third composite material, the mass ratios of the inner core, the lithium iron manganese phosphate coating layer with a manganese-iron ratio of 8:(2-1), the lithium iron manganese phosphate coating layer with a manganese-iron ratio of 7:(3-2), the lithium iron manganese phosphate coating layer with a manganese-iron ratio of 6:(4-3), the lithium iron manganese phosphate coating layer with a manganese-iron ratio of 5:(5-4), the lithium iron manganese phosphate coating layer with a manganese-iron ratio of 4:(6-5), the lithium iron manganese phosphate coating layer with a manganese-iron ratio of 3:(7-6), the lithium iron manganese phosphate coating layer with a manganese-iron ratio of 2:(8-7), and the lithium iron manganese phosphate coating layer with a manganese-iron ratio of 1:(9-8) are (1-10):(1-20):(3-13):1:1:1:1:1:1:

1.

16. A secondary battery, characterized in that: The positive electrode material of the secondary battery includes the polyphosphate positive electrode material as described in any one of claims 1 to 10, or includes the polyphosphate positive electrode material prepared by the method as described in any one of claims 11 to 15.

Citation Information

Patent Citations

  • Cathode material LiMn1-xFexPO4 for lithium ion cell and preparation method of cathode material LiMn1-xFexPO4

    CN104577119A

  • Positive electrode active material

    CN106129328A